Effects of cyclin-dependent kinase activity on the coordination of growth and the cell cycle in green algae at different temperatures - Zachleder, Vilém; Ivanov, Ivan; Vítová, Milada; Bišová, Katerina (Journal of experimental botany, 2019)
The progression of the cell cycle in green algae dividing by multiple fission is, under otherwise unlimited conditions, affected by the growth rate, set by a combination of light intensity and temperature. In this study, we compared the cell cycle characteristics of Desmodesmus quadricauda at 20 °C or 30 °C and upon shifts between these two temperatures. The duration of the cell cycle in cells grown under continuous illumination at 20 °C was more than double that at 30 °C, suggesting that it was set directly by the growth rate. Similarly, the amounts of DNA, RNA, and bulk protein content per cell at 20 °C were approximately double those of cells grown at the higher temperature. For the shift experiments, cells grown at either 20 °C or 30 °C were transferred to darkness to prevent further growth, and then cultivated at the same or the other temperature. Upon transfer to the lower temperature, fewer nuclei and daughter cells were produced, and not all cells were able to finish the cell cycle by division, remaining multinuclear. Correspondingly, cells placed in the dark at the higher temperature divided faster into more daughter cells than the control cells. These differences correlated with shifts in the preceding cyclin-dependent kinase activity, suggesting that cell cycle progression was not related to growth rate or cell biomass but correlated with cyclin-dependent kinase activity.
Keywords: cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Darkness; nízká teplota; Chlorophyta; bílkoviny řas; tma; buněčný cyklus; Cell Cycle; vysoká teplota; Algal Proteins; Hot Temperature; Cold Temperature